Demystifying Real-Time IoT Streaming and Analytics in the Cloud - Uppalapati, Venkata Karunakar (International Journal of Computing and Engineering, 2025)
Within the connected online environment, real-time IoT analytics has become the trending topic of discussion, mainly illustrated as a maze of manifesting technicalities. However, there is a secret under this impression, which is a cool, down-to-earth architecture based on the four most important stages: collection, movement, processing, and action. Edge devices murmur information over secured paths, and message brokers smooth creamy traffic variations, leaving breathing room to the downstream services. Stream processing engines bring raw numbers to life, converting mysterious telemetry into business-actionable insights in milliseconds. The insights that result branch to automatic feedback and archival depositories that allow instant response and long-term education. These systems are handed a series of security blankets, ranging from device certificates to creating a network isolation between the device and the rest of the world, and thrive in a cloud system where resources grow and shrink in perfect unison with true demand. This article demystifies the technical babble to lay bare the beauty of simplicity that lurks behind the sophisticated IoT implementations that allow technical teams to reduce the huge gap between the technical models and the reality of implementation. With the aid of this architectural clarity, institutions are now able to harness the power of connected devices without being overwhelmed by the details of the implementation of security holes.